Wild Food Harvest, Food Security, and Biodiversity Conservation in Jamaica: A Case Study of the Millbank Farming Region - Campbell, Donovan; Moulton, Alex A.; Barker, David; Malcolm, Tashana; Scott, Lance; Spence, Adrian; Tomlinson, Jhannel; Wallace, Tiffany (Frontiers in Sustainable Food Systems, 2021)
Harvesting wild food is an important coping strategy to deal with food insecurity in farming households across the Caribbean. The practice is tightly connected to the region’s unique agrarian history, food heritage, traditional cuisine, and local knowledge of wild or semidomesticated plants. In Jamaica, small-scale farmers are the chief stewards of agrobiodiversity, and their food security and wellbeing are often dependent on wild food harvest. Yet, there is a paucity of empirical research on the relationship between wild food use, food security, and biodiversity conservation. In this paper, we use the knowledge and lived experience of rural farmers in a remote community (Millbank) at the edge of the Blue and John Crow Mountains National Park (BJMNP) to explore the relationship between wild food harvest and food insecurity within the context of protected area management. Specifically, we seek to 1) characterize differential patterns of wild food harvest; 2) examine the relationship between food insecurity and wild food harvest, and 3) explore the implications of forest conservation measures for wild food harvest. Detailed interviews were conducted with 43 farmers to capture data on food insecurity, wild food collection, livelihood satisfaction, household characteristics, farming activities, livelihood strategies, and forest resource interaction. The Food Insecurity Experience Scale (FIES) was used to characterize food insecurity, while participatory techniques were used to develop indicators to assess the wellbeing of farmers. The results show strong evidence of a relationship between wild food harvest and food insecurity (p<0.001). Overall, the findings support the importance of wild foods to the wellbeing of rural households and provide empirical evidence for its inclusion in food security, poverty, and biodiversity conservation policies.